X-Ray Radiative Transfer Calculation Based on a Physics-based Model of the Subparsec-scale Gases around an Active Galactic Nucleus and Its Application to NGC 3783 - Atsushi Tanimoto; Keiichi Wada; Hirokazu Odaka; Yuki Kudoh; Nozomu Kawakatu (The Astrophysical Journal)
Although the X-ray spectra of Seyfert 1 galaxies exhibit absorption lines of He-like iron and H-like iron at blueshifted velocities of approximately 500 km s ^−1 , the physical origin of these absorption lines remains uncertain. In this study, we performed X-ray radiative transfer based on the subparsec-scale thermally driven outflows. The initial step involved calculating the photoionization equilibrium using the Cloudy code, which is based on three-dimensional radiative hydrodynamic simulations. Subsequently, X-ray radiative transfer was performed using the Monte Carlo Simulation for Astrophysics and Cosmology code. Our findings indicate that when the angle of inclination ranges within 55°–65°, the transmitted component of the X-ray spectrum displays absorption lines of He-like and H-like iron, exhibiting a blueshift of approximately 500 km s ^−1 . The results suggest that the absorption lines are generated by a photoionized gas within 0.005 pc. Additionally, the results indicate that the scattered component of the X-ray spectrum exhibits emission lines originating from neutral iron fluorescence, He-like iron, and H-like iron. The emission lines are broadened by approximately 7000 km s ^−1 due to the Keplerian rotation. Furthermore, the model reproduced the H-like iron and H-like iron absorption lines in NGC 3783 observed by the Chandra High Energy Transmission Grating.